Efectiveness of Facebook Advertising in the Context of a Small Manufacturer of Home Decorations - Santusová, Michala (2022)
The thesis analyzes different advertisement executions to unfold which segment of the target audience, focusing on age and gender solely, is the most effective within the context of a small Slovak manufacturer of home decorations. Firstly, an analysis of a previously run campaign was carried out, and after, an experiment followed. Effectiveness, or responsiveness, of these target audiences was measured by the CPC indicator, which were monitored on two sets of ads in the experiment – the first contrasted a video ad with a photo ad, the second compared a product ad with an ad featuring the owner’s face. Both secondary data and the experiment were conducted through the Facebook’s advertising tool Ads Manager within the bounds of the author’s own soy candle company LAVINA. The most crucial finding was that overall, , the most effective segment of the target audience within the experiment proved to be men aged between 35 and 44. Between product and face ads, it is the most effective to target men aged 45-54 and for photo and video ads, the best is to again target 35-44 men. Additionally, both hypotheses got rejected, which suggests the results of both the analysis and the experiment differ from existing literature. However, this might be rooted in the circumstances under which the experiment ran.